1991
DOI: 10.1007/bf02660597
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heating to prevent deterioration of cottonseed during storage

Abstract: Fuzzy cottonseed samples of 14.5% moisture and <1.0% free fatty acids (FFA) contents heated in a conventional, home-style microwave oven at 700W and 2450 MHz for intervals up to 2.0 min. The 2.0-min treatment reduced the moisture content to 13.1%. Examination of the seed immediately after microwave heating (MWH) indicated no differences in the proteins or in the quality or quantity of the cotton linters as compared with unheated seed. Neither the oil content of the seed nor the quality of the oil were affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This was in sharp contrast to the study by Hentges et al (1991), who reported slight changes in solubility of different protein fractions from cowpeas with storage. However, a dramatic reduction in the salt-soluble or water-soluble protein as a result of adverse storage was reported in other seeds (Conkerton et al, 1991;Saio et al, 1980). Protein Thermal Stability.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This was in sharp contrast to the study by Hentges et al (1991), who reported slight changes in solubility of different protein fractions from cowpeas with storage. However, a dramatic reduction in the salt-soluble or water-soluble protein as a result of adverse storage was reported in other seeds (Conkerton et al, 1991;Saio et al, 1980). Protein Thermal Stability.…”
Section: Resultsmentioning
confidence: 94%
“…Among the functional properties of proteins, solubility is the most critical one because it affects many others, such as foaming and emulsifying capacity and gelling ability (Kinsella, 1976). Changes in total protein extractability/solubility with storage have been reported in soybeans (Nash et al, 1971;Saio et al, 1980) and cottonseeds (Conkerton et al, 1991). Changes in solubility of different protein fractions with storage were also reported with cowpeas (Hentges et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Tung nuts were collected at Poplarville, Mississippi, in 1992. Tung oil was extracted with petroleum ether as described by Conkerton et al (7). Duplicate, representative samples of the oils and oilfree meals were used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Oil extraction~ The oil was extracted from tung kernels with petroleum ether according to the procedure of Conkerton et aL (12). A typical extraction was as follows: Dry kernels (2.5 g) were placed in a Stomacher bag with 100 mL of petroleum ether, then extracted in a Stomacher Lab-Blender 400 (Tekmar C(x, Cincinnati, OH) for 2.5 rain_ The oil was collected by filtration, and petroleum ether was removed by evaporation under nitrogen.…”
Section: Methodsmentioning
confidence: 99%